2022
DOI: 10.1002/jrs.6314
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities and evolution of Raman spectra of multilayer Ge/Si(001) heterostructures containing arrays of low‐temperature MBE‐grown Ge quantum dots of different size and number density: Experimental studies and numerical simulations

Abstract: Ge/Si(001) multilayer heterostructures containing arrays of low‐temperature self‐assembled Ge quantum dots and very thin SixGe1−x layers of varying composition and complex geometry have been studied using Raman spectroscopy and scanning tunneling microscopy (STM). The dependence of Raman spectra on the effective thickness of deposited Ge layers has been investigated in detail in the range from 4 to 18 Å. The position and shape of both Ge and SiGe vibrational modes are of great interest because they are closely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…7 , the Ge–Ge peak of each sample has a different degree of frequency shift compared to the intrinsic peak of Ge bulk material at 300.5 cm −1 . Many existing reports 14 , 43 , 44 have pointed out that in heteroepitaxial material systems, compressive strain can cause the Raman peak to move away from the intrinsic peak and towards the high wave number (blue shift), while dislocation defects, quantum confinement effect, and tensile strain make the Raman peak shift from intrinsic position to low wave number (red shift). The blue shift of the Ge–Ge peak in samples Ge 2.0 and Ge 2.4 is caused by the compressive strain accumulated in the Ge film as described in Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 , the Ge–Ge peak of each sample has a different degree of frequency shift compared to the intrinsic peak of Ge bulk material at 300.5 cm −1 . Many existing reports 14 , 43 , 44 have pointed out that in heteroepitaxial material systems, compressive strain can cause the Raman peak to move away from the intrinsic peak and towards the high wave number (blue shift), while dislocation defects, quantum confinement effect, and tensile strain make the Raman peak shift from intrinsic position to low wave number (red shift). The blue shift of the Ge–Ge peak in samples Ge 2.0 and Ge 2.4 is caused by the compressive strain accumulated in the Ge film as described in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to many advantages, such as compatibility with Si-based technology, long carrier lifetime, δ-shaped density of states, strong response to near-infrared and mid-infrared bands, etc., Ge quantum dots (QDs) have shown a wide range of applications in optoelectronic devices 1 8 and attracted a lot of research work 9 11 . Over the past 30 years, Ge QDs have been grown mainly by materials equipment with low deposition rates (~ 0.01–0.04 Å/s), such as molecular beam epitaxy (MBE) 12 14 , chemical vapor deposition (CVD) 15 18 , and solid phase epitaxy (SPE) 19 , their corresponding complete technical system has been formed. In recent years, the idea of exploring the growth of Ge QDs has been further broadened, some work using typical physical vapor deposition (PVD) techniques such as ion beam sputtering 20 , high-vacuum evaporation 21 , e-gun deposition 22 , 23 to prepare Ge QDs has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…As the development of research, multilayer QDs t the requirement of photonic device in a structure and improve device performance effectively [5,6]. In the past decade, the researchers mainly focused on single-layer growth technics of QDs, multi-layer QDs prepared methods also had been explored by the conventional low-rate deposition technics, such as molecular beam epitaxy (MBE) [7,8], chemical vapor deposition (CVD) [9] and modi ed chemical vapor deposition (MCVD) [10]. In the growth technics mentioned, high requirements for temperature control (MBE), the reaction products may become surface impurities (CVD), especially the high cost of equipment and maintenance, and low deposition rate, have become major obstacles to the industrialization of highquality QDs.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, much research mainly focused on single-layer growth technics of QDs, multi-layer QDs prepared methods also had been explored by the conventional low-rate deposition technics, such as molecular beam epitaxy (MBE) [7,8] and chemical vapour deposition (CVD) [9,10]. Some recent typical work on multi-layer Ge/Si QDs involves that Chu et al [11] reported the work of using low growth temperature (Ge below 400 • C, Si below 500 • C) to inhibit the formation of Ge nano islands in multi-layer Ge/Si films grown by low-pressure CVD to fabricate and demonstrate stacked Ge nanosheets GAA FET CMOS inverter, Storozhevykh et al [7] studied the influence of the critical thickness and stress distribution of the intermediate layers formed in the Ge/Si heterostructure on atomic mixing and structure of multi-layer Ge/Si QDs grown by MBE, Smagina et al [12] manufactured multi-layer Ge/Si QDs with ordered spatial arrangement and novel photoluminescence properties by adjusting the parameters (diameter and spatial period) of pits on the SOI substrate and depositing Si isolation layers with appropriate thickness (25 nm) based on MBE technology. In the growth technics mentioned, high requirements for temperature control (MBE), the reaction products may become surface impurities (CVD), especially the high cost of equipment and maintenance, and low deposition rate, have become major obstacles to the industrialization of high-quality QDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation